Studies on the incidence of Reproductive Abnormalities in Local non-descript Female Goats - SHEKHAR REDDY, K CHANDRA; REDDY, V SUDHIR CHANDRA; RAO, A SESHAGIRI; REDDY, J MURALIDHAR; SHARMA, G P (The Indian Journal of Animal Reproduction, 2023)
An abattoir study was done on the local non-descript female goat genitalia to study the incidence of various forms fgynaecopathological condition and the same was worked out to be 10.86 percent. The detailed incidence of various types of gynaeco-pathological conditions are as follows: Hypoplasia of ovary (0.03 per cent); Abnormal shape of ovary (0.03per cent); double external os of cervix (0.10 per cent); Bent cervix ( 1.70 per cent); uterus unicornis (0.03 per cent); Parovarian cysts (2.22 per cent); ovarian cyst& (0.27 per cent); ovaro-bursal adhesions (0.31per cent); salpingitis (0.51 per cent); Hydrosalpinx (0.20 per cent); Endometritis (3.?-1 percent); Hydrometra (0.06 per cent); Melanin pigmentation (0.06 percent); False extra-uterine pregnancy (0.03 per cent); Foetal mummification (0.06 per cent); foetal maceration (0.03 per cent); Foetal anasarca . (0.03 per cent); Anky losed muscle contracture monster (0.3 percent) and Hydrocephalus (0.03 per cent).